Mathematical Communication Skills in Terms of Cognitive Style - Sugianto Sugianto; St. Budi Waluya; YL. Sukestiyarno; Wardono Wardono (Universitas Negeri Semarang, 2022)
The goal of this study is to help students improve their mathematical communication abilities, which are shown in indicators based on cognitive style. up to 30 students may participate in learning mathematics logic in class X SMAIQu Al-Bahjah Center. The methodology is qualitative. Through the use of surveys, exams, interviews, and documentation, data were gathered. Techniques for data analysis include data gathering, data reduction, data display, and data verification. Based on the questionnaire's answers, the subjects were divided into three categories or levels of cognitive style: low, medium, and high. Each survey had two participants. According to the study's findings, students' mathematical communication abilities include indicators for formulating mathematical concepts and strategies, expressing themselves verbally and in writing, visualizing mathematical concepts, understanding, interpreting, and evaluating mathematical material ideas verbally and in writing, as well. Use terminology, mathematical notation, and structures to show ideas and explain connections between mathematical concepts in various visual formats.